2018
DOI: 10.1177/0963689718780307
|View full text |Cite
|
Sign up to set email alerts
|

Human peripheral blood mononuclear cells enriched in endothelial progenitor cells via quality and quantity controlled culture accelerate vascularization and wound healing in a porcine wound model

Abstract: The transplantation of endothelial progenitor cells (EPCs) is used to promote wound angiogenesis. In patients with chronic wounds and accompanying morbidities, EPCs are often compromised in number and function. To overcome these limitations, we previously developed a quality and quantity controlled (QQ) culture system to enrich peripheral blood mononuclear cells (PBMNCs) in EPCs. To evaluate the wound healing efficacy of mononuclear cells (MNCs) harvested after QQ culture (QQMNCs), preclinical studies were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
3
17
0
1
Order By: Relevance
“…Granulation tissue is composed of fibroblasts and extracellular matrix including collagens. In the matrix, neovascularization takes place by angiogenesis and vasculogenesis [ 11 ]. These events finally terminate after full epidermal coverage of the wounded surface.…”
Section: Introductionmentioning
confidence: 99%
“…Granulation tissue is composed of fibroblasts and extracellular matrix including collagens. In the matrix, neovascularization takes place by angiogenesis and vasculogenesis [ 11 ]. These events finally terminate after full epidermal coverage of the wounded surface.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the administration of CCL2 can promote neovascularization by affecting the migration of EPCs, as well as macrophages, which have crucial impacts on neovascularization. This was further supported by the observation that EPCs induced to migrate by the CCL2-CCR2 axis could contribute to neovascularization, an indispensable event sustaining newly formed granulation tissue (Kado et al, 2018;Spring et al, 2005). Moreover, VEGF also induced in vitro EPC migration as CCL2 did.…”
Section: Discussionmentioning
confidence: 66%
“…Accumulation of peripheral blood CD133+ cells in the renal tissue are likely to promote kidney regeneration. Moreover, in the rodent studies, CD133 ‘progenitor’ cells reported may not exist in the mouse kidney nor in the bone marrow, whether the therapeutic effects of the cells are due to autocrine, paracrine or endocrine effects still remain controversial 23,5457 . Our results showed that premobilization of CD133+ cells prior to CPB significantly abated IAKI while mobilization of CD133+ cells after CPB procedure couldn’t prevent IAKI efficiently.…”
Section: Discussionmentioning
confidence: 99%